2016
DOI: 10.17269/cjph.107.5652
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index (BMI) and percent body fat among BMI-defined non-obese middle-aged individuals: Insights from a population-based Canadian sample

Abstract: OBJECTIVES:To evaluate the association between percent body fat (%BF) and body mass index (BMI) among BMI-defined non-obese individuals between 40 and 69 years of age using a population-based Canadian sample. DATA AND METHODS:Cross-sectional data from the Canadian Health Measures Survey (2007 and) was used to select all middle-aged individuals with BMI < 30 kg/m 2 (n = 2,656). %BF was determined from anthropometric skinfolds and categorized according to sex-specific equations. Association of other anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Potentially, the characterization of obesity by body mass, which is common in these studies, may be inappropriately representing body composition. We have shown, in a healthy and overweight population cohort, that body mass index (BMI) inappropriately estimates body composition in 30% of the population, with a specific disparity between BMI and body composition measurements in healthy females (Collins et al, 2017c ). Also, there is a lack of data describing the effect of obesity on muscle integrity, and a lack of consistent protocols to assess muscle strength (Tomlinson et al, 2016 ).…”
Section: Obesity and Impact On Muscle Integritymentioning
confidence: 99%
“…Potentially, the characterization of obesity by body mass, which is common in these studies, may be inappropriately representing body composition. We have shown, in a healthy and overweight population cohort, that body mass index (BMI) inappropriately estimates body composition in 30% of the population, with a specific disparity between BMI and body composition measurements in healthy females (Collins et al, 2017c ). Also, there is a lack of data describing the effect of obesity on muscle integrity, and a lack of consistent protocols to assess muscle strength (Tomlinson et al, 2016 ).…”
Section: Obesity and Impact On Muscle Integritymentioning
confidence: 99%
“…The present study revealed that both CAVI and carotid IMT had a positive association with metabolic syndrome defined by a VFA ≥ 100 cm 2 . Nagayama et al in their study reported a negative rela-ratus, could be a useful tool for distinguishing body fat from other body compositions, such as bone and muscle, but it has not to date been sufficiently validated and, thus, is often used in combination with BMI [33][34][35][36][37] . Moreover, percent body fat is totally calculated without the separation of subcutaneous and visceral fat content.…”
Section: General Obesitymentioning
confidence: 99%
“…Furthermore, OA management strategies and obesity prevention interventions [33] are most effective in the long-run when they are targeted to patients with overweight (BMI-defined non-obese) at early stages of the disease process [34]. As such, Manninen et al [35] highlights the need to identify candidates for OA prevention and management strategies in the middle-aged and the non-obese.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also demonstrated that overweight (BMI between 25 to 30 kg/m 2 ) during middle adulthood may play an important role in OA’s initiation and progression [ 31 , 32 ]. Furthermore, OA management strategies and obesity prevention interventions [ 33 ] are most effective in the long-run when they are targeted to patients with overweight (BMI-defined non-obese) at early stages of the disease process [ 34 ]. As such, Manninen et al [ 35 ] highlights the need to identify candidates for OA prevention and management strategies in the middle-aged and the non-obese.…”
Section: Introductionmentioning
confidence: 99%